Influence of DC/DC Converter Control on Source Current Ripple of the Switched Reluctance Motor - Mateusz Daraż; Piotr Bogusz (Energies)
This paper presents a solution to reduce source current ripple in the electrical power supplying a switched reluctance motor (SRM) drive. Source current ripple negatively affects the power source by introducing a variable frequency component and increasing losses in the power source. Reducing the source current ripple is important, especially in battery electric vehicles (BEVs). The solution proposed in this paper for reducing source current ripple is to use a classic DC/DC boost converter connected in series with the SRM power supply system. The key to reducing source current ripple is the DC/DC converter control method proposed and described in this article. This method involves controlling the DC/DC converter synchronized with the speed of the SRM motor DC/DC. To verify the correct operation of the proposed solution, simulation and laboratory tests of an SRM drive were performed, the results of which are shown in this paper.